Biphasic Effect of Basic Fibroblast Growth Factor on Anterior Pituitary Folliculostellate TtT/GF Cell Coupling, and Connexin 43 Expression and Phosphorylation. (October 2015) - Vitale, M. L.; Barry, A.
<x xml:space="preserve">Abstract</x> Basic fibroblast growth factor (bFGF) is a mitogenic and differentiating cytokine. In the anterior pituitary, folliculostellate (FS) cells constitute the major source of bFGF. bFGF affects endocrine cell proliferation and secretion in the anterior pituitary. In addition, bFGF increases its own expression by acting directly on FS cells. FS cell Cx43‐mediated gap junction intercellular communication allows the establishment of an intrapituitary network for the transmission of information. In the present study, we assessed how bFGF regulates FS cell coupling. Time course studies were carried out on the FS cell line TtT/GF. Short‐term bFGF treatment induced a transient cell uncoupling and the phosphorylation in Ser368 of membrane‐bound Cx43 without modifying Cx43 levels. We demonstrated the involvement of the protein kinase C (PKC) isoform α in the phosphorylation of Cx43 in S368. Moreover, we showed that bFGF induced PKCα activation by stimulating its expression, phosphorylation and association with the plasma membrane. The long‐term incubation with bFGF increased TtT/GF cell coupling, total Cx43 levels and Cx43 accumulation at the cell membrane of cytoplasmic projections. The Cx43 level increase was a result of the stimulation of Cx43 gene transcription as mediated by the extracellular‐regulated kinase 1/2 signalling pathway. Taken together, the data show that bFGF modulates TtT/GF cell coupling by activating different pathways that lead to opposite effects on Cx43 phosphorylation and expression depending on the duration of the exposure of the cells to bFGF. A short‐term bFGF exposure reduces cell‐to‐cell communication as a mean of desynchronising FS cells. By contrast, long‐term exposure to bFGF enhances cell‐to‐cell communication and facilitates coordination among FS cells.